login
Expansion of Product_{k>=0} (1 - x^(2^k))^(2^(k+1)).
1

%I #13 Nov 06 2018 06:43:23

%S 1,-2,-3,8,-6,4,26,-56,-7,70,-51,32,120,-272,-200,672,-182,-308,1026,

%T -1744,-660,3064,-916,-1232,2466,-3700,-3990,11680,-1416,-8848,13752,

%U -18656,-8503,35662,-14331,-7000,27122,-47244,-29870,106984,-25895,-55194,140173,-225152

%N Expansion of Product_{k>=0} (1 - x^(2^k))^(2^(k+1)).

%F Equals the self-convolution of A321327.

%F G.f.: A(x) satisfies A(x) = ((1 - x) * A(x^2))^2, with A(0) = 1.

%F a(n) = A321327(2*n) for n >= 0.

%Y Cf. A073708, A321327, A321335.

%K sign

%O 0,2

%A _Seiichi Manyama_, Nov 05 2018